Variasi Kata “Bagaimana” dalam Bahasa Jawa di Wilayah Perbatasan Kabupaten Malang dan Blitar - Dwi Ira Ningrum Mardinan (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The aim of this article is to describe the variation of the word “Bagaimana” in Javanese which is spoken by the society in the border area of Malang and Blitar Regency. The theories contained in this article are sociolinguistic, dialectology, and dialect. The method used is descriptive qualitative and with unstructured interviews with eighteen informants. The result is the variation word “Bagaimana” in Javanese in the border area has three variations, namely “piye”, “yo’opo” and “yo’piye”. The word “yo’piye” is a unique vocabulary for the term “Bagaimana” in Javanese in this area, because the word “Yo’piye” comes from the word “yo’opo” which is spoken by the people in Malang Regency and the word “piye” spoken by the people in Blitar.